Block type anion exchange membrane with interstitial alkyl chain and preparation method of block type anion exchange membrane
By designing block biphenyl polymers with gap alkyl chains, the shortcomings of existing anion exchange membranes in terms of conductivity, dimensional stability and alkali resistance are solved, and a high-performance anion exchange membrane is achieved.
Patent Information
- Application Number
- CN202411867797.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing anion exchange membranes have shortcomings in high conductivity, dimensional stability and alkali resistance, which limits the development of fuel cells and electrolytic water technology.
Block biphenyl polymers with gap alkyl chains were designed to prepare microphase separations through block structures, the introduction of flexible alkyl chains reduced the rigidity of the polymer, and enhanced alkali resistance through an ether-bonded backbone design.
It achieves high conductivity, improves the flexibility and alkali resistance of the membrane, and improves the performance of fuel cells and electrolytic water technology.
Smart Images

Figure CN119708508A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer electrolyte membranes, and in particular relates to a block type anion exchange membrane with interstitial alkyl chains and a preparation method thereof. Background Art
[0002] Fuel cells and water electrolysis technologies can achieve efficient conversion and circulation of hydrogen energy and various forms of energy, and promote the realization of the goals of "carbon neutrality and carbon peak". Anion exchange membrane fuel cells (AEMFCs) and anion exchange membrane water electrolysis (AEMWEs) technologies used in alkaline environments are widely regarded as key technologies for the development of hydrogen energy because they can use non-precious metal catalysts and relatively low-cost anion exchange membranes to replace expensive perfluorosulfonic acid membranes. Anion exchange membranes (AEMs) are the core components of this type of hydrogen energy conversion technology and have received widespread attention from researchers in recent decades. At present, some commercial anion exchange membranes have been developed, such as Fumasep, Sustainion and Aemion membranes. However, they still have shortcomings such as low conductivity, poor dimensional stability and poor alkali resistance, which seriously limit the development of AEMFCs and AEMWEs.
[0003] The study found that increasing the ion exchange capacity of the membrane can effectively improve the conductivity of the electrolyte membrane, but at the same time it will also cause excessive water absorption into the membrane, resulting in excessive swelling and a decrease in mechanical properties. Constructing a hydrophilic / hydrophobic microphase separation structure inside the polymer can provide a high-speed channel for ion transmission, while the hydrophobic phase in the membrane can effectively limit the swelling of the membrane.
[0004] Recent studies have found that if there are weak polar bonds (such as ether bonds) in the polymer molecular structure, the polymer main chain is susceptible to OH-nucleophilic attack under high temperature and high alkaline environment, resulting in decreased alkali resistance of AEMs. Designing and preparing polymer skeletons (such as polyaromatic rings or polyolefins) without weak bonds as polymer main chains has become a mainstream method to improve the alkali resistance of AEMs. However, on the one hand, due to its weak intermolecular interaction, the polyolefin structure causes excessive swelling and poor thermal stability of polyolefin-based AEMs. On the other hand, the rigidity of traditional polyaromatic rings is usually large, resulting in poor film-forming and flexibility of AEMs. AMEs based on these two types of main chains need to be further designed and modified to improve the performance of the membrane. Therefore, it is urgent to develop an AEMs with high conductivity, high dimensional stability and high alkali resistance to meet the practical application of hydrogen energy conversion devices. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a block anion exchange membrane with high conductivity, high dimensional stability and high alkali resistance. Starting from the molecular level, a block biphenyl polymer with interstitial alkyl chains is designed and prepared. Microphase separation is constructed in the polymer membrane through the block structure to improve the conductivity; interstitial alkyl chains are introduced into the main chain of AEMs to reduce the rigidity of polybiphenyl and improve the flexibility of the membrane; and the main chain design without ether bonds is used to enhance the alkali resistance of the polymer electrolyte membrane.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is: a block anion exchange membrane with interstitial alkyl chains, whose general chemical structure includes repeating units as shown below:
[0007]
[0008] In the formula, n is the length of the interstitial alkyl chain, which is an integer of 2 to 12; x is the content of the biphenyl unit, which is greater than 0 and less than 1; and m represents the degree of polymerization.
[0009] Another object of the present invention is to provide a method for preparing a high-performance block anion exchange membrane with interstitial alkyl chains, which mainly comprises the following steps:
[0010] (a) Synthesis of α,ω-diphenylethane
[0011] The tetrahydrofuran solution of n-butyl lithium was slowly added to the dehydrated toluene at -78°C and stirred at room temperature for 3 hours. Then α,ω-dihaloalkane was added to the reaction solution and reacted at room temperature for 12 to 24 hours. The reaction solution was quenched with water and extracted with ethyl acetate. The extract was dried to obtain a crude product, which was finally separated and purified by column chromatography to obtain the target α,ω-diphenylalkane.
[0012] The molar ratio of n-butyl lithium to α,ω-dihaloalkane is 2:1, the molar ratio of toluene to α,ω-dihaloalkane is greater than 2:1, the separation and purification eluent is n-hexane, and the stationary phase is silica gel.
[0013] (b) Preparation of block polymers
[0014] Biphenyl and 4-imidazole carboxaldehyde were dissolved in dichloromethane (material concentration was 10-30 wt %, and the molar amount of 4-imidazole carboxaldehyde was 1.1 times that of biphenyl), and a mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (volume ratio 3:4) was added under an ice-water bath, and prepolymerized under an ice-water bath for 5 hours to obtain a prepolymer solution 1.
[0015] The α,ω-diphenylethane and 4-imidazole carboxaldehyde in step (a) are dissolved in dichloromethane (the material concentration is 10-30wt%, and the molar amount of 4-imidazole carboxaldehyde is 1.1 times that of α,ω-diphenylethane), and a mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (volume ratio 3:4) is added under an ice-water bath, and prepolymerized under an ice-water bath for 5 hours to obtain a prepolymer solution 2.
[0016] Finally, the two prepolymer solutions are mixed and further mechanically stirred at room temperature for 12 to 24 hours. The mixture becomes highly viscous and is washed out with deionized water until the washing liquid is neutral to obtain a fibrous block polymer with interstitial alkane chains.
[0017] The ratio of the two prepolymer solutions ensures that the content of biphenyl or α,ω-diphenyl alkyl group is respectively greater than 0 and less than 1 and the overall sum is 1.
[0018] (c) Quaternization
[0019] The block polymer in step (b) is dissolved in dimethyl sulfoxide, potassium carbonate and iodomethane are added (the molar ratio of potassium carbonate to polymer is 2:1, and the molar ratio of iodomethane to polymer is 1:10), and the reaction is stirred at 60°C for 24 hours. The reaction solution is precipitated with ethanol and washed with water to obtain the target quaternized polymer. Finally, the quaternized polymer is redissolved in dimethyl sulfoxide, the membrane solution is dripped into a clean glass mold, and placed in an oven at 80°C to dry into a film. Finally, the membrane is immersed in a 60°C potassium hydroxide solution for 24 hours for ion replacement to obtain an OH-type anion exchange membrane.
[0020] The block type anion exchange membrane with interstitial alkane chains prepared by the present invention can be applied to the fields of fuel cells, liquid flow batteries, water electrolysis, electrodialysis or separation membranes.
[0021] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0022] (1) The design of the block structure is conducive to the construction of microphase separation inside the membrane, thereby providing a high-speed channel for ion transmission and improving ion conductivity. At the same time, the hydrophobic phase can limit the excessive swelling of the membrane;
[0023] (2) Introducing flexible interstitial alkyl chains into rigid polybiphenyl can improve the flexibility of aromatic polymers and enhance their film-forming ability;
[0024] (3) The design of a main chain without weak bonds (such as ether bonds) can effectively enhance the alkali stability of AEMs. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the H NMR spectrum of 1,6-diphenylhexane synthesized in Example 1.
[0026] Figure 2 The following are the H NMR spectrum of the block biphenyl polymer prepared in Example 2 (a); the H NMR spectrum of the block biphenyl polymer prepared in Example 3 (b); the H NMR spectrum of the block biphenyl polymer prepared in Example 4 (c) and the H NMR spectrum of the random copolymer biphenyl polymer in Comparative Example 1 (d).
[0027] Figure 3 H2 / O2 fuel cell performance of the block AEMs with interstitial alkyl chains prepared in Example 3 and the random copolymer AEMs in Comparative Example 1. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with some specific embodiments.
[0029] Example 1
[0030] (a) At -78°C, under nitrogen protection, n-butyl lithium (8 mL, 20 mmol, 2.5 M n-hexane solution) was slowly dripped into 10 mL of dehydrated toluene. Then, 10 mL of dehydrated tetrahydrofuran was slowly dripped. The mixture was reacted at room temperature for 3 hours, and then 1,6-dibromohexane (2.44 g, 10 mmol) was slowly added, and the mixture was continued to react at room temperature for 12 hours. The reaction solution was quenched with water, extracted with ethyl acetate, and the organic layer was dried to obtain a crude product, which was finally separated and purified by n-hexane column chromatography to obtain clean 1,6-diphenylhexane.
[0031] (b) Stir and dissolve biphenyl (1.54 g, 10 mmol) and 4-imidazole carboxaldehyde (1.05 g, 11 mmol) in 10 mL of dichloromethane. Slowly add a mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (6 mL / 8 mL) under an ice-water bath, and mechanically stir and prepolymerize for 5 hours to obtain a prepolymer solution 1. Stir and dissolve 1,6-diphenylhexane (2.38 g, 10 mmol) and 4-imidazole carboxaldehyde (1.05 g, 11 mmol) in 10 mL of dichloromethane. Slowly add a mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (6 mL / 8 mL) under an ice-water bath, and mechanically stir and prepolymerize for 5 hours to obtain a prepolymer solution 2. Finally, mix the two and continue mechanical stirring for 24 hours. The reaction solution becomes highly viscous and is poured into deionized water for precipitation and washing until the washing liquid is neutral to obtain a fibrous block polymer.
[0032] (c) The block polymer in step (b) is dissolved in dimethyl sulfoxide, followed by adding potassium carbonate and iodomethane (the molar ratio of potassium carbonate, iodomethane to polymer is 2:10:1), stirring and reacting at 60°C for 12 hours, then pouring the reaction solution into ethanol for precipitation and washing, followed by further washing with water, and finally drying to obtain a quaternized block polymer. The quaternized block polymer is redissolved in dimethyl sulfoxide, and the membrane solution is poured into a clean glass mold and dried in an oven at 80°C to form a film. Finally, the membrane is immersed in a 60°C potassium hydroxide solution for 24 hours for ion replacement to obtain an OH-type anion exchange membrane. The structural formula of the target AEMs obtained is as follows:
[0033]
[0034] The water absorption, swelling degree, and ionic conductivity of the prepared AEMs were 72%, 26%, and 115 mS cm at 80 °C. -1 The tensile strength and elongation at break in the wet state are 15 MPa and 152% respectively; at 80°C, the H2 / O2 fuel cell performance can reach 1.21 W cm -2 ; 1A cm at 60°C -2 At the current density, the voltage of the electrolytic water tank is 2.05V.
[0035] Example 2
[0036] Example 2 is similar to Example 1, except that the α,ω-dihaloalkane selected in step (a) is 1,2-dibromoethane, and 1,2-diphenylethane is prepared.
[0037] In addition, during the prepolymerization of step (b), biphenyl (2.31 g, 15 mmol) and 4-imidazole carboxaldehyde (1.59 g, 16.5 mmol) were stirred and dissolved in 15 mL of dichloromethane. A mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (9 mL / 12 mL) was slowly added under an ice-water bath, and mechanical stirring was performed for prepolymerization for 5 hours. At the same time, 1,2-diphenylethane (0.91 g, 5 mmol) and 4-imidazole carboxaldehyde (0.53 g, 5.5 mmol) were stirred and dissolved in 10 mL of dichloromethane. A mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (3 mL / 4 mL) was slowly added under an ice-water bath, and mechanical stirring was performed for prepolymerization for 5 hours. Finally, the two were mixed and mechanical stirring was continued for 24 hours. The reaction solution became highly viscous and was poured into deionized water for precipitation and washing until the washing solution was neutral to obtain a fibrous block polymer.
[0038] The structural formula of the target AEMs obtained is as follows:
[0039]
[0040] The water absorption, swelling degree, and ionic conductivity of the prepared AEMs were 40%, 16%, and 76 mS cm at 80 °C. -1 ; The tensile strength and elongation at break in the wet state are 29MPa and 77%; At 80℃, the performance of H2 / O2 fuel cell can reach 0.81W cm -2 ; 1A cm at 60°C -2 At the current density, the voltage of the electrolytic water tank is 2.58V.
[0041] Example 3
[0042] Example 3 is similar to Example 2, except that during the prepolymerization in step (b), biphenyl (1.54 g, 10 mmol) and 4-imidazole carboxaldehyde (1.05 g, 11 mmol) are stirred and dissolved in 10 mL of dichloromethane. A mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (6 mL / 8 mL) is slowly added under an ice-water bath, and mechanical stirring is performed for prepolymerization for 5 hours. At the same time, 1,6-diphenylethane (1.82 g, 10 mmol) and 4-imidazole carboxaldehyde (1.05 g, 11 mmol) are stirred and dissolved in 10 mL of dichloromethane. A mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (6 mL / 8 mL) is slowly added under an ice-water bath, and mechanical stirring is performed for prepolymerization for 5 hours. Finally, the two are mixed and mechanical stirring is continued for 24 hours. The reaction solution becomes highly viscous and is poured into deionized water for precipitation washing until the washing liquid is neutral to obtain a fibrous block polymer.
[0043] The structural formula of the target AEMs obtained is as follows:
[0044]
[0045] The water absorption, swelling degree, and ionic conductivity of the prepared AEMs were 48%, 19%, and 88 mS cm at 80 °C. -1 ; The tensile strength and elongation at break in the wet state are 25MPa and 110%; At 80°C, the H2 / O2 fuel cell performance can reach 0.92W cm -2 ; 1A cm at 60°C -2 At this current density, the voltage of the electrolytic water tank is 2.42V.
[0046] Example 4
[0047] Example 4 is similar to Example 2, except that during the prepolymerization in step (b), biphenyl (0.77 g, 5 mmol) and 4-imidazole carboxaldehyde (0.53 g, 5.5 mmol) are stirred and dissolved in 5 mL of dichloromethane. A mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (3 mL / 4 mL) is slowly added under an ice-water bath, and mechanical stirring is performed for prepolymerization for 5 hours. At the same time, 1,6-diphenylethane (2.73 g, 15 mmol) and 4-imidazole carboxaldehyde (1.59 g, 16.5 mmol) are stirred and dissolved in 15 mL of dichloromethane. A mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid (9 mL / 12 mL) is slowly added under an ice-water bath, and mechanical stirring is performed for prepolymerization for 5 hours. Finally, the two are mixed and mechanical stirring is continued for 24 hours. The reaction solution becomes highly viscous and is poured into deionized water for precipitation and washing until the washing liquid is neutral to obtain a fibrous block polymer.
[0048] The structural formula of the target AEMs obtained is as follows:
[0049]
[0050] The water absorption, swelling degree, and ionic conductivity of the prepared AEMs were 54%, 22%, and 105 mS cm at 80 °C. -1 ; The tensile strength and elongation at break in the wet state are 19MPa and 139%; At 80°C, the H2 / O2 fuel cell performance can reach 1.07W cm -2 ; 1A cm at 60°C -2 At this current density, the voltage of the electrolytic water tank is 2.18V.
[0051] Example 5
[0052] Example 5 is similar to Example 1, except that the α,ω-dihaloalkane selected in step (a) is 1,12-dibromododecane to prepare 1,12-diphenyldodecane. The monomer ratio during prepolymerization in step (b) is the same as that in Example 1. The structure of the obtained AEMs is as follows:
[0053]
[0054] The water absorption, swelling degree, and ionic conductivity of the prepared AEMs were 84%, 35%, and 122 mS cm at 80 °C. -1 ; The tensile strength and elongation at break in the wet state are 11MPa and 172%; At 80°C, the H2 / O2 fuel cell performance can reach 1.28W cm -2 ; 1A cm at 60°C -2 At this current density, the voltage of the electrolytic water tank is 1.95V.
[0055] Example 6
[0056] Example 6 is similar to Example 1, except that the α,ω-dihaloalkane selected in step (a) is 1,4-dibromobutane to prepare 1,4-diphenylbutane. The monomer ratio during prepolymerization in step (b) is the same as that in Example 1. The structure of the obtained AEMs is as follows:
[0057]
[0058] The water absorption, swelling degree, and ionic conductivity of the prepared AEMs were 60%, 23%, and 108 mS cm at 80 °C. -1 ; The tensile strength and elongation at break in the wet state are 20MPa and 132%; At 80°C, the performance of H2 / O2 fuel cells can reach 1.02W cm -2 ; 1A cm at 60°C -2 At the current density, the voltage of the electrolytic water tank is 2.20V.
[0059] Comparative Example 1
[0060] Comparative Example 1 prepared a random copolymer AEMs with the same molecular formula as Example 3. The preparation method is to stir and dissolve biphenyl (1.54g, 10mmol), 1,6-diphenylhexane (1.82g, 10mmol) and 4-imidazole carboxaldehyde (2.11g, 22mmol) in 20mL of dichloromethane. Slowly add trifluoromethanesulfonic acid and methanesulfonic acid (12mL / 16mL) mixed acid under an ice-water bath, continue mechanical stirring for 48 hours, the reaction solution becomes highly viscous, pour it into deionized water for precipitation and washing, until the washing liquid is neutral, and obtain a fibrous random polymer. The random polymer is dissolved in dimethyl sulfoxide, followed by the addition of potassium carbonate and iodomethane (the molar ratio of potassium carbonate, iodomethane to polymer is 2:10:1), stirred at 60°C for 12 hours, and then the reaction solution is poured into ethanol for precipitation and washing, followed by further washing with water, and finally dried to obtain a quaternized random polymer. The quaternized random polymer was redissolved in dimethyl sulfoxide, and the membrane solution was poured into a clean glass mold and dried in an oven at 80°C to form a membrane. Finally, the membrane was immersed in a 60°C potassium hydroxide solution for 24 hours for ion replacement to obtain an OH-type anion exchange membrane. The structural formula of the prepared random AEM is shown below:
[0061]
[0062] The water absorption, swelling degree, and ionic conductivity of the prepared AEMs were 35%, 10%, and 68 mS cm at 80 °C. -1 ; The tensile strength and elongation at break in the wet state are 36MPa and 48%; At 80°C, the H2 / O2 fuel cell performance can reach 0.58W cm-2 ; 1A cm at 60°C -2 At this current density, the voltage of the electrolytic water tank is 2.73V.
[0063] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable technicians familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A block anion exchange membrane with interstitial alkyl chains, characterized in that: The chemical structure of the block anion exchange membrane is a repeating unit shown in the following formula: In the formula, n is the length of the interstitial alkyl chain, which is an integer of 2 to 12; x is the content of the biphenyl unit, which is greater than 0 and less than 1; and m represents the degree of polymerization.
2. A method for preparing a block anion exchange membrane with interstitial alkyl chains according to claim 1, characterized in that: The preparation method steps are as follows: (a) Synthesis of α,ω-diphenylethane A tetrahydrofuran solution of n-butyl lithium is added to dehydrated toluene at -78°C and stirred at room temperature for 3 hours, then α,ω-dihaloalkane is added to the reaction solution, and the reaction is carried out at room temperature for 12 to 24 hours, the reaction solution is quenched with water, and extracted with ethyl acetate, and the extract is dried to obtain a crude product, and finally separated and purified by column chromatography to obtain the target product α,ω-diphenylalkane; (b) Preparation of block polymers ① Dissolve biphenyl and 4-imidazole carboxaldehyde in dichloromethane, add a mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid in an ice-water bath, and prepolymerize in an ice-water bath for 5 hours to obtain a prepolymer 1 solution; ② Dissolve the α,ω-diphenylethane and 4-imidazole carboxaldehyde in step (a) in dichloromethane, add a mixed acid of trifluoromethanesulfonic acid and methanesulfonic acid under an ice-water bath, and prepolymerize under an ice-water bath for 5 hours to obtain a prepolymer 2 solution; ③ The two prepolymer solutions are mixed and mechanically stirred at room temperature for 12 to 24 hours. The mixture becomes highly viscous. The mixture is washed out with deionized water until the washing liquid is neutral to obtain a fibrous block polymer with interstitial alkane chains. (c) Quaternization The block polymer in step (b) is dissolved in dimethyl sulfoxide, potassium carbonate and iodomethane are added, and the reaction is stirred at 60° C. for 24 hours. The reaction solution is precipitated with ethanol and washed with water to obtain a quaternary ammonium polymer; finally, the quaternary ammonium polymer is redissolved in dimethyl sulfoxide, the solution is dripped into a clean glass mold, and placed in an oven at 80° C. to dry into a film, and the film is immersed in a 60° C. potassium hydroxide solution for 24 hours for ion replacement to obtain an OH-type anion exchange membrane.
3. The method for preparing a block anion exchange membrane with interstitial alkyl chains according to claim 2, characterized in that: In step (a), the molar ratio of n-butyl lithium to α,ω-dihaloalkane is 2:1, the molar ratio of toluene to α,ω-dihaloalkane is greater than 2:1, the separation eluent is n-hexane, and the stationary phase is silica gel.
4. The method for preparing a block anion exchange membrane with interstitial alkyl chains according to claim 2, characterized in that: In step (b), the concentration of biphenyl and 4-imidazole carboxaldehyde in dichloromethane is 10-30wt%, the molar amount of 4-imidazole carboxaldehyde is 1.1 times that of biphenyl, and the volume ratio of trifluoromethanesulfonic acid to methanesulfonic acid is 3:
4.
5. The method for preparing a block anion exchange membrane with interstitial alkyl chains according to claim 2, characterized in that: In step (b), the concentration of α,ω-diphenyl alkane and 4-imidazole carboxaldehyde in dichloromethane is 10-30wt%, the molar amount of 4-imidazole carboxaldehyde is 1.1 times that of α,ω-diphenyl alkane, and the volume ratio of trifluoromethanesulfonic acid to methanesulfonic acid is 3:
4.
6. The method for preparing a block anion exchange membrane with interstitial alkyl chains according to claim 2, characterized in that: In step (b), the ratio of the two prepolymer solutions ensures that the content of biphenyl or α,ω-diphenylalkyl group is respectively greater than 0 and less than 1, and the total sum is 1.
7. The method for preparing a block anion exchange membrane with interstitial alkyl chains according to claim 2, characterized in that: In step (c), the molar ratio of potassium carbonate to polymer is 2:1, and the molar ratio of methyl iodide to polymer is 1:
10.
8. An application of the block anion exchange membrane with interstitial alkyl chains according to claim 1, characterized in that: The block type anion exchange membrane is applied to fuel cells, liquid flow batteries, water electrolysis, electrodialysis or separation membranes.
Citation Information
Patent Citations
Eight-armed polyethylene glycol derivative, preparation method and related biological substance modified by derivative
CN104877127A
Method for preparing micro-nano metal organic framework by oil-water two-phase method and application of micro-nano metal organic framework
CN118344611A
Polyarylimidazole polymer, preparation and hydrogen ion selective membrane
CN118620152A
Poly (fluorene-co-alkyl)-based anion exchange membrane and preparation method thereof
CN118684924A
Preparation of aromatic hydrocarbons
US3787512A
Cited By
Crosslinking type polyion liquid block copolymer as well as preparation method and application thereof
CN121975071A